Sustainable Plastic Waste Collection and Distribution Strategies in Operations Management - Dhriti Kappagantu; Netra Mahindra; Baseedu Sai Sandeep; Krishna Mayi (PT Agung Media Publisher, 2025)
The global plastic waste crisis necessitates effective collection and distribution strategies aligned with principles of Operations Management and Sustainability. This study investigates efficient methods for managing plastic waste, focusing on mechanisms such as buy-back facilities, door-to-door collection systems, and reverse vending machines (RVMs). Among the various types of plastics, only PET, HDPE, PP, and LDPE are widely recyclable, with PET being the most preferred due to its high recyclability and potential for reuse in manufacturing. A mixed-methods approach was adopted, combining both qualitative and quantitative data collection techniques. The study involved a comparative analysis of different plastic collection strategies across various countries and regions, including deployments of RVMs in the UK, Sweden, Australia, Canada, the USA, and selected Indian cities such as Mumbai, Delhi, and Chennai. Findings reveal that RVMs offer a superior method for plastic collection due to their integrated sorting capabilities and user-friendly design. The global proliferation of over 100,000 RVM units illustrates their scalability and acceptance. Furthermore, the study highlights the environmental and economic benefits of optimized plastic waste collection, including natural resource conservation, energy savings, job creation, and reduced ecological impact. The integration of sustainable collection strategies, particularly through the deployment of RVMs, holds significant promise for enhancing waste management systems. The study emphasizes the importance of selecting appropriate technologies and infrastructures to support a circular economy. These insights contribute to operational improvements in waste logistics and support long-term sustainability goals.